CONTINUITY OF MIDWIFERY CARE FOR A PREGNANT WOMAN WITH FIRST-DEGREE PERINEAL LACERATION AT RIMENDA TARIGAN CLINIC, MEDAN DENAI SUB-DISTRICT, MEDAN CITY, NORTH SUMATRA PROVINCE, YEAR 2025 - Ester Junita Gultom; Herna Rinayanti Manurung; Kismiasih Adethia; Aflah Hasibuan; Dina Sandriana Br Tumangger; Elsamonika Nduru; Rinda Permata Sari , (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Maternal health is a key priority in improving overall public health. Indonesia has a high maternal mortality rate (MMR) of 305 deaths per 100,000 live births, largely due to postpartum hemorrhage. One contributing factor is perineal rupture, which affects 75% of vaginal births. WHO reports 2.7 million global cases, with projections reaching 6.3 million by 2050. To reduce the MMR to 70 by 2030, in line with the SDGs, the Indonesian government is working to improve women and children's health services. First-degree perineal lacerations, often caused by spontaneous tears or episiotomy, are manageable by midwives under existing health regulations. Midwifery care must be systematic, starting from data collection to problem identification, followed by planning, action, and evaluation using methods like SOAP and the Helen Varney model. The Continuity of Care (CoC) model supports integrated care across healthcare facilities—from pregnancy to postpartum—helping reduce maternal mortality and improve outcomes for both mothers and babies.